Quasi-experimental research designs - Thyer, Bruce A. (New York ; Oxford : Oxford University Press, 2012)
This pocket guide describes the logic, design, and conduct of the range of such designs, encompassing pre-experiments quasi-experiments making use of a control or comparison group and time-series designs.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Mar. 5, 2012).
Keywords: Social sciences -- Research -- Methodology; Research -- Methodology